ANALISIS PENGARUH WAKAF PRODUKTIF TERHADAP KESEJAHTERAAN MASYARAKAT DI MUKIM MATANG PANYANG - Munardi Munardi; Damanhur Damanhur; Mulyana Fitri (Faculty of Economics and Business, Universitas Malikussaleh, 2020)
This study aimed to determine the effect of productive endowment on community welfare in Matang Panyang. This study used primary data obtained by distributing questionnaires to 30 respondents who were selected using the Purposive sampling technique. The data analysis method used was a simple linear regression method with the help of EVIEWS. Based on the test of the correlation coefficient of 0.837835, it showed that productive endowment had a strong relationship to improve community welfare. Based on the coefficient determination test, it showed that productive endowment had an effect of 70.19% on community welfare. From the results of the study, it revealed that productive endowment (X) significantly influenced the welfare community (Y). Based on the t-value of 8.120918 and the t-table value of 2.04841 with a significant level of 0.0000, it concluded that these tests accepted Ha and rejected Ho.